2006
DOI: 10.2166/wh.2006.031
|View full text |Cite
|
Sign up to set email alerts
|

The health effects of flooding: social research results from England and Wales

Abstract: This paper presents interview survey data by social scientists using established health measures on the health effects of flooding for residents in 30 locations in England and Wales. Firstly, it examines the extent to which flooded residents reported suffering physical and psychological health effects during and after the event. Secondly, it explores the issue of whether these effects were long-lasting by comparisons with the general population and with those at risk but not flooded. In the study, about two th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 18 publications
12
149
0
2
Order By: Relevance
“…Identified by Kates (1962) and frequently confirmed since (e.g. Tunstall et al, 2006;Grothmann and Reusswig, 2006), this disinterest can discourage decision-makers from investing time and resources in the needs of such communities and lead to them being, in effect, disenfranchised:…”
Section: Routes Of Accountability and The Discourse Of Public Opinionmentioning
confidence: 99%
“…Identified by Kates (1962) and frequently confirmed since (e.g. Tunstall et al, 2006;Grothmann and Reusswig, 2006), this disinterest can discourage decision-makers from investing time and resources in the needs of such communities and lead to them being, in effect, disenfranchised:…”
Section: Routes Of Accountability and The Discourse Of Public Opinionmentioning
confidence: 99%
“…Previous research in this field has found that both degree of exposure (e.g., Neria et al, 2008;Norris et al, 2002;Vernberg et al, 1996) and relocation (e.g., Acierno et al, 2007;Bland et al, 1996;Galea et al, 2005;Yzermans et al, 2005) are associated with an increased risk of poor psychological outcomes. Similarly, in the UK, Tunstall et al (2006) found that the degree of flooding was a predictor for psychological distress. This study rate of PTSD was higher than found by Uttervall et al (2014) in study of Swedish adolescents aged 16-19 years, who had experienced the 2004 tsunami and participated in a follow-up study 19 months' post-disaster females seemed to a higher extent than males to suffer from mental health problems after the tsunami disaster, 26.9% compared with 17.3% for males.…”
Section: Discussionmentioning
confidence: 87%
“…Exposure to post-disaster stressors also appears to impact upon the psychological health of people exposed to events, for example lack of water, sanitation, electricity, adversity in housing reconstruction, were associated with an increased risk of developing PTSD following hurricane Katrina Tunstall et al, 2006). Furthermore, there is also evidence to suggest that depression and anxiety are common sequelae of natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…These overflows result in an increase of bacteria, which can be assessed quantitatively (e.g., Karrasch et al 2009;ten Veldhuis et al 2010). Social studies on health effects are generally assessed qualitatively by questionnaires (e.g., Tapsell et al 2002;Tunstall et al 2006). Flood related environmental effects are not well studied, except for many regional environmental impact assessments (Mostert and Junier 2009).…”
Section: Implementation Of the Floods Directive In Flandersmentioning
confidence: 99%